2017
DOI: 10.1016/j.neuropsychologia.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolic correlates of attention networks in Alzheimer's Disease: A study of the Stroop

Abstract: Patients with Alzheimer’s Disease (AD) show difficulties with attention. Cognitive neuroscience models posit that attention can be broken down into alerting, orienting, and executive networks. We used the Stroop Color-Word test to interrogate the neural correlates of attention deficits in AD. We hypothesized that the Word, Color, and Color-Word conditions of the Stroop would all tap into the alerting and orienting networks. The Color-Word condition would additionally tap into the executive network. A ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…TMT‐B time provides a measure of executive function associated with working memory . SCWT, an executive function test that measures executive inhibition of irrelevant responses, which might be associated with alerting, orienting, and executive network, did not correlate with the CNR of the LC. Consistent with our findings, a previous study investigating the association between TMT‐B and other neuropsychological measures via multiple regression analysis indicated performance in the TMT‐B test only weakly correlated with that of SCWT .…”
Section: Discussionmentioning
confidence: 96%
“…TMT‐B time provides a measure of executive function associated with working memory . SCWT, an executive function test that measures executive inhibition of irrelevant responses, which might be associated with alerting, orienting, and executive network, did not correlate with the CNR of the LC. Consistent with our findings, a previous study investigating the association between TMT‐B and other neuropsychological measures via multiple regression analysis indicated performance in the TMT‐B test only weakly correlated with that of SCWT .…”
Section: Discussionmentioning
confidence: 96%
“…The STROOP is a valid, reliable, and widely used measure of selective attention, representing the monitoring aspect of executive attention ( Melrose et al, 2017 ). Our outcome of interest was the “naming interference tendency”, which is obtained by subtracting the median reaction time of the naming baseline condition from the naming interference condition.…”
Section: Methodsmentioning
confidence: 99%
“…Six of these studies reported significant cognitive improvements after learning a foreign language ( Bak et al, 2016 ; Pfenninger and Polz, 2018 ; Bubbico et al, 2019 ; Wong et al, 2019 ; Long et al, 2020 ; Meltzer et al, 2021 ). Most notably, these improvements occurred in tasks measuring aspects of executive attention (e.g., the STROOP task, Simon task, Test of Everyday Attention) ( Melrose et al, 2017 ). However, two of the four studies applying these tasks had only a quasi-experimental design ( Bak et al, 2016 ; Long et al, 2020 ), and one was a pilot study without a control group ( Pfenninger and Polz, 2018 ).…”
Section: Introductionmentioning
confidence: 99%